Bathyal Joeropsididae (Isopoda: Asellota) from south-eastern Australia, with description of two new genera - Just, J. (Memoirs of the Victorian Museum, 2001)
Fifty-three species of Joeropsis, listed here, have been previously described in this, until now, the only genus of the family. Characters in the Joeropsididae are tabulated and discussed to ascertain which may be diagnostic at family and genus level. J. bicarinata sp. nov., Rugojoeropsis rugosa gen. nov., sp. nov., Scaphojoeropsis multicarinata gen. nov., sp. nov., and S. kimblae sp. nov. are described from the lower shelf and upper bathyal of southeastern Australia. All are strongly sculptured dorsally.
World Isopoda DB